The effects of resveratrol on myocardial ischemia-reperfusion injury - (Experimental study) - Siraci, G; Rahman, A; Burma, O; Akar, I; Uysal, A; Ozercan, IH; Ilhan, N (Medimond Publishing Co, 2005)
Myocardial ischemia-reperfusion injury is a frequent problem that is observed after coronary interventions. In this study, 30 rabbits were separated to 5 groups randomly. Group I (sham group), group 2 (I/R group without treatment), group 3 (ethanol group), group 4 (preischemia resveratrol group) and group 5 (prereperfusion resveratrol group). Rabbits were subjected to 3 hours reperfusion followed by 30 minutes left anterior descenden (LAD) coronary artery occlusion. To the rabbits in group 4 and in group 5, resveratrol was administered as intravenous bolus. After 3 hours reperfusion, malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and nitric oxide (NO center dot) levels were measured in the blood and heart tissue samples. Heart tissues were examined histopathologically. Tissue and serum MDA levels were higher in myocardial ischemia reperfusion groups than sham group. But this increase in group 4 was less than group 2 and 3. In resveratrol administered groups compared with control groups, there were no statistically significant changes at other parameters.
6th International Congress on Coronary Artery Disease -- OCT 29-NOV 01, 2005 -- Istanbul, TURKEY
Keywords: Red Wine